Performance and microbial community of an electric biological integration reactor (EBIR) for treatment of wastewater containing ibuprofen. (February 2019) - Feng, Yan; Long, Yingying; Wang, Zhongwei; Wang, Xinwei; Shi, Nan; Suo, Ning; Shi, Yulong; Yu, Yanzhen
Highlights: EBIR for wastewater treatment containing ibuprofen were operated for 196 days. Higher removal rates of ibuprofen, COD and NH4 + -N were attained in EBIR than BAF. Optimal conditions of EBIR were CD 12.73 A/m 2, HRT 3.5 h and ibuprofen 0.08 mg/L. Microbial community in EBIR and single BAF were analyzed at the optimal conditions. EBIR is a highly efficient alternative technology to wastewater containing ibuprofen. Abstract: Electric biological integration reactor (EBIR) was designed and built for the treatment of wastewater containing ibuprofen. This study evaluates the removal performance of EBIR by comparison with biological aerated filter (BAF), while also discussing the optimal operational parameters of EBIR within the context of the response surface methodology. The results indicate that EBIR exhibits higher average removal rates of ibuprofen, chemical oxygen demand (COD) and NH4 + -N, i.e. 93.48%, 86.72% and 85.19%, representing an increase by 61.59%, 14.57% and 10.49%, respectively, compared with BAF. The optimal conditions for EBIR were 12.73 A/m 2 current density (CD), 3.5 h hydraulic retention time and 0.08 mg/L influent ibuprofen concentration. In addition, microbial community structures were detected using an Illumina Miseq PE300 system, which were different at the phylum, class, and genus levels between EBIR and BAF. The microbial communities of EBIR, including mainly Trichococcus, Aeromonas, Saprospiraceae_uncultured, Thiobacillus, Aeromonas Flavobacterium, Sphingopyxis, Candidate_division_TM7_norank, Acinetobacter and physicochemical properties indirectly confirmed the excellent removal performance at 12.73 A/m 2 CD.